2006
DOI: 10.1176/jnp.18.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Perception of Affective Prosody in Schizophrenia

Abstract: The authors aimed to explore schizophrenia patients' ability to perceive affective prosody. Specifically, certain emotions that may be more troublesome for patients and possible gender differences in prosody perception were assessed. Thirty six schizophrenia patients and 32 age-, education-, and gender-matched healthy comparison subjects assessed on an affective prosody test were examined. Patients were impaired on recognition of affective prosody overall, and their difficulties with prosody perception may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 31 publications
13
44
5
Order By: Relevance
“…Unlike a previous study on the recognition of emotional prosody (Bozikas et al 2006), we found no association of any of the performance measures with gender.…”
Section: Association Of Emotional Prosody Identification With Other Pcontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike a previous study on the recognition of emotional prosody (Bozikas et al 2006), we found no association of any of the performance measures with gender.…”
Section: Association Of Emotional Prosody Identification With Other Pcontrasting
confidence: 99%
“…speech melody) is another important source for nonverbal emotional communication. Several studies have addressed deficits in schizophrenia in order to identify emotional prosody using different kinds of stimuli (Edwards et al 2001(Edwards et al , 2002Kucharska-Pietura et al 2005 ;Leitman et al 2005 ;Bozikas et al 2006 ;Matsumoto et al 2006). These studies found evidence for impaired recognition in acute and chronic schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehension of emotional prosody is crucial for social functioning [28] and compromised in various psychiatric disorders, including schizophrenia (deficits for anger and sadness), [29], bipolar affective disorder (deficits for fear and surprise) [30], and depression (deficits for surprise) [31]. Future research might apply an approach similar to ours to clarify whether these deficits are paralleled by activity changes blurring emotions at the level of the AC or are due to disrupted patterns within frontal regions [32,33] reflecting biased interpretation of emotional signals.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some literature suggests that antipsychotics may impact the variables studied here, although the direct influence is uncertain. 137 It should be noted that this sample is in rehabilitation and is largely made up of medication users. In addition, the relationships between motivation scores and role functioning scores may be inflated because they are rated during the same interview, although raters are trained to avoid these problems.…”
Section: Discussionmentioning
confidence: 99%